Frontier machine learning techniques for melanoma skin cancer identification and categorization: An in-Depth review - Viomesh Singh; Kavita A. Sultanpure; Harshwardhan Patil (Oral Oncology Reports)
Skin cancer stands as one of the prevalent and life-threatening malignancies, witnessing a substantial global surge in reported cases. Failure to diagnose it at its incipient stages may lead to metastasis, significantly elevating mortality rates. Early detection, however, presents a curative prospect. Thus, the prompt and precise diagnosis of skin cancers remains a paramount focus in current research. Numerous machine learning techniques have been seamlessly woven into the fascinating world of computer-aided skin cancer diagnosis and figuring out if that blemish is a real troublemaker. Machine learning is like the Sherlock Holmes of artificial intelligence. It's got these brainy models and algorithms that not only soak up information but also play psychic by predicting stuff on brand new data it's never laid eyes on before. In contrast to the conventional biopsy method, which is both laborious and costly, machine learning algorithms offer a viable alternative for early detection, reducing the burden on specialists while concurrently augmenting the diagnostic accuracy of skin lesions. In this article we delve into a thorough exploration of cutting-edge machine learning methods that play a crucial role in identifying those sneaky signs of skin cancer. I took a deep dive into the pool of relevant studies, offering you an insider's look into the performance of the friendly neighborhood the k-nearest neighbor approach, the robust SVM, and the sophisticated CNN. In the review we Openly discussed the inherent limitations and quirks of each algorithm, affording them the spotlight they deserve.